How much is too much information? Testing the effects of digital feedback on fisher behavior and governance in coastal small-scale fisheries - McClanahan, Tim; Kosgei, Jesse; Longobardi, Lorenzo; Tilley, Alexander (Frontiers in Sustainable Food Systems, 2025)
The proposed research protocol aims to evaluate the effects of digital information on behavior change in small-scale reef fisheries. The study addresses the challenges of sustainable fisheries management, particularly in environments where collective action is necessary but difficult to achieve due to diverse stakeholder behaviors and preferences. Utilizing the Knowledge-Attitude-Practice framework, the study will implement and test the WorldFish Peskas digital monitoring system across various Beach Management Units (BMUs) in Kenya. The experimental design includes five intervention levels, ranging from a control group with minimal information feedback to treatments providing increasingly localized and disaggregated. These interventions will be assessed using a Before-After-Control-Impact (BACI) approach. The study will test three heuristic models of human behavior: the information deficit model, the self-interested actor model, and the neighborhood interested actor model. These models will guide the interpretation of outcomes, which include changes in fishing practices, governance participation, and socio-economic benefits. The research will run over a 2-year period, with data collection on variables such as fishing patterns, compliance with regulations, and community well-being. Ultimately, this study seeks to inform policy on the effectiveness of digital tools in promoting sustainable fishing practices and improving livelihoods in coastal communities. The findings will provide governments and conservation organizations with a communication framework to better balance ecological sustainability with community needs.